Study of Offshore Patrol Vessel Models for Seakeeping and Maneuvering Improvement using Anti-Rolling Fins. Issue 1 (January 2022) - Asmara, I P S; Sumardiono; Alfanda, B D; Abdullah, K; Rochmad, A N
Abstract: Offshore patrol vessel models using anti-rolling fins with variations of fin angle and shape are investigated in this study to improve the seakeeping and maneuvering performances, especially in the combat operation of the vessel. This study focused on the determination of the effect of adding fins to the seakeeping and maneuvering performances by optimizing fin angle and shape fitted on the ship hull. The 3D ship model with three variations of fin's shape and four variations of the fin angle was analyzed using a numerical method of computational fluid dynamic (CFD) software. Result showed that fins type NAIAD 525, has the smallest average roll response occurs at 55 deg fin with motion amplitude 5.4E-05 deg. At the same fin angle, the average pitch amplitude reaches the smallest of 2.7E-03 deg. For PRAXIS type, the smallest average roll response occurs at 60 deg fin with motion amplitude 4.7E-05 deg. But for average pitch amplitude, the lowest value occurs at 45 deg of 2.7E-03 deg. And WESMAR type, the smallest average roll response occurs at 45 deg fin with motion amplitude 3.9E-05 deg. At the same fin angle, the average pitch amplitude reaches the smallest of 2.7E-03 deg. Turning maneuvers parameter of the vessel are comply with the IMO standard. The highest value of Tactical Diameter, which is 4.91 L, occurs in condition of no environmental disturbance, while the highest value of Advance occurs in wind disturbance condition with a value of 4.29 L.